IoT based air components collection for machine learning reinforcement - Islam, Tanjima; Rabbi, Fahad; Ahmed, Rushana; Rahman, Md Muhtashemur; Ahmed, Mashrur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.